Increasing MSME Sales With Social Media Marketing - Saiyed, Rahma; Nia Suryani, Ade; Nindya Putri, Andiena (Yayasan Pendidikan Belajar Berdikari, 2024)
The purpose of this study is to better understand MSME Alunicorn's Instagram-based digital marketing approach for increasing sales of its headscarf goods. The study was carried out qualitatively, with a case study design. Data collection methods include interviews, observations, and documentation. The study participants were Alunicorn MSME owners and marketing personnel. The study's findings suggest that Alunicorn has utilized digital marketing methods such as content optimization, promotions, and digital consumer services. However, the approach in place is still not optimal in terms of SEO optimization, content variety, promotional frequency, and consumer review management. Alunicorn's digital marketing approach is still limited in terms of human resources and finance. As a result, Alunicorn is encouraged to enhance human resource capacity, digital marketing skills, implement the latest technology, and analyze consumer data in order to optimize its strategy and boost product sales in a sustainable manner.